The dynamics of the condition of athletes depending on organization of training activities high-speed power orientation - Pan Yuantsyuan; Kozhedub M.S.; Vrublevskiy E.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to discern objective trends that reveal the correlation between the performance of female sprinters and the extensive training regimen they undergo in speed and strength training during the initial phases of the annual cycle. Methods and structure of the study. Seven young sprinters, aged between 15 and 17, were observed for a period of thirteen weeks. Their specific physical abilities were evaluated through a series of tests, including a ten-fold jump from a standing position and measurements of muscle strength in the isometric mode while extending the leg at the knee and hip joints. The frequency of these tests was two to three times a month, and it was adjusted to coincide with the phases of each athlete’s OMC. Results and conclusions. It was discovered that during the initial six weeks of the program, the athletes experienced a statistically significant decrease in both absolute and explosive strength in the leg extensor muscles, as well as a decline in their performance in the tenfold jump. The subsequent reduction in the jumping and strength training (from the seventh to the thirteenth week) resulted in a substantial improvement in speed and strength indicators. The observed phenomenon in the course of the study aligns with a general biological pattern observed when applying substantial training effects that require a substantial mobilization of energy resources and can disrupt the body’s homeostasis, leading to the development of long-term adaptive changes.